Physical activity engagement among young people living in the care system: A narrative review of the literature. (August 2019) - Bruce, Lauren; Pizzirani, Bengianni; Green (nee Cox), Rachael; Quarmby, Thomas; O'Donnell, Renée; Strickland, David; Skouteris, Helen
Abstract: Young people living in care are among the most vulnerable groups in the community, have often experienced trauma, and exhibit a wide range of adverse physical and mental health outcomes. Physical activity (PA) is a health behaviour associated with numerous physical, psychological and social health benefits, yet research indicates that a majority of young people in care are not meeting the minimum recommended levels of PA. To date, there is a paucity of research that has specifically examined factors associated with PA engagement in the care population. A narrative review was conducted to summarise the literature examining outcomes for young people in care who engage in PA, and the barriers and facilitators of PA engagement among young people living in care. Findings of the review suggest that there are multiple factors that may impact young people in care from engaging in PA, including physical, psychological, family, interpersonal, and societal/environmental level factors. Given the unequivocal benefits of increased physical activity, empirical research is required to more comprehensively examine these factors in the care environment and should be couched within a trauma-informed approach. Highlights: Physical activity has numerous benefits for the physical, psychological and social health and well-being of young people Young people living in care could benefit from increased levels of physical activity engagement A number of individual and external factors can be barriers or facilitators of physical activity among young people in care Targeting factors that influence physical activity among young people in care should be a key focus for care-providers